Factors associated with never treatment and acceptability of mass drug administration for the elimination of lymphatic filariasis in Guyana, 2021. - Claudia Duguay; Reza A Niles-Robin; Charles R Thickstun; Horace Cox; Annastacia Sampson; Jean Seme-Fils Alexandre; Nathely Caleb-Mars; Charles W Goss; Ana Morice; Ronaldo G Carvalho Scholte; Alison Krentel (Public Library of Science (PLoS), 2024)
Guyana remains one of four countries in the Americas endemic for lymphatic filariasis (LF). Elimination of LF requires repeated annual mass drug administration (MDA) with sufficient levels of coverage for success. This study assesses the acceptability and never treatment of LF MDA using data from a routine assessment survey in 2021. A subset of individuals, over 20 years of age (n = 2498), were selected to receive an expanded questionnaire to examine factors associated with acceptability and never treatment. Assessed factors include respondent demographics, knowledge, risk perceptions of LF, and opinions on the MDA programme. The majority (73%) of those with scores above the acceptability threshold (score ≥22.5) reported participating in MDA two or more times. Factors strongly and positively associated with scoring above the acceptability threshold include beliefs in importance of participation in MDA for their community (aOR = 2.8, 95%CI (1.1-7.2)), perception of importance of LF treatment (6.9 (3.2-14.7)), receiving treatment in 2021 (2.9 (1.5-5.4)), and the number of self-reported times taking treatment for LF (2.2 (1.1-4.4)). Ten percent of respondents participated in the MDA for the first time in 2021, while 15% reported never treatment during any round of LF MDA. Three factors were statistically associated with participation in MDA across the two levels of the models (level 1: took LF treatment once versus never, and level 2: took LF treatment twice versus never) included: 1) scoring above the acceptability threshold (aOR = 6.2, 95%CI(3.8-10.0)), 2) self-reported importance of participation in MDA for their community (7.1 (2.9-17.8)), and 3) personal beliefs that they should take LF treatment even if they are not sick (2.6 (1.7-3.9)). As Guyana moves closer to LF elimination, these results provide further insight and understanding into programmatic results and could inform further action following MDA activities-particularly if an approach is needed to address never treatment during MDA.